AN ANALYSIS OF ROMANTIC ASPECT AS PORTRAYED IN ‘THE REVOLT IN PARADISE” BY K’TUT TANTRI - Shokhikhatul Khasanah (JEELL (Journal of English Education, Linguistics and Literature) English Department of STKIP PGRI Jombang, 2019)
This study was aimed to analyze the aspects of Romanticism manifested in the novel “The Revolt in Paradise” and behavior of character reflects Romanticism in “The Revolt in Paradise”. This study was based on the descriptive-qualitative research since the findings were going to be presented in a descriptive form. The data to be analyzed are gathered from two sources. The primary source is the novel itself; The Revolt in Paradise and the secondary sources includes many appropriate documents in the form of literary works, previous thesis, biography, theories and literary criticism, dictionaries and etc. Related to the instrument, the researcher employed herself as the human instrument. The data were analyzed through underlying and labeling. The result of the study found that there four aspects of Romanticism manifested in the novel; The Revolt in Paradise, they were: the love of nature, the memories of the past, the horror /gothic setting and the emotion; included; love, anger and hatred. This study also found that The Revolt in Paradise gave the vivid depiction of the Nationalism as the major behavior reflects Romanticism.